Relationship between knowledge management, innovation and organization performance: An empirical study in Vietnamese small and medium-sized enterprises - Phạm Anh Tuấn; Phạm Quốc Trung (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2021)
This study is based on the research model of Valdez-Juárez, García-Pérez de Lema, and Maldonado-Guzmán (2016) and related theories aim to examine the relationship between knowledge management, innovation and organizational performance in Vietnamese SMEs. The results show that factors of employee training, corporate strategy and policy, acquiring employee's knowledge, and organizational culture have a positive impact on innovation and innovation has a positive impact on organizational performance. From the results of this study, the study also proposes a number of recommendations to help SMEs effectively apply knowledge management, thereby improving their capacity to innovate and improve organizational performance.